Effects of a high energy and low protein diet on hepatic and plasma characteristics and Cidea and Cidec mRNA expression in liver and adipose tissue of laying hens with fatty liver hemorrhagic syndrome. (6th December 2018) - Peng, Gang; Huang, Enfu; Ruan, Jiming; Huang, Liumei; Liang, Haiping; Wei, Qing; Xie, Xianhua; Zeng, Qingjie; Huang, Jianzhen
Abstract: Cidea and Cidec are two members of Cell death‐inducing DNA fragmentation factor‐alpha‐like effector family proteins, which could be involved in lipid or fat metabolism. To better understand the roles of Cidea and Cidec in fatty liver hemorrhagic syndrome (FLHS), 150 healthy 155‐day‐old Hyline Brown laying hens were randomly divided into control group (fed with basic diet) and experimental group (fed with high‐energy low‐protein [HELP] diet). Analysis of the liver by tissue sectioning and hematoxylin and eosin staining showed that the HELP diet induced micro‐vesicular steatosis in laying hens. Subsequently, based on the liver color scores and the range of lipid accumulation observed in histological examination, we classified livers with <50% vacuolization as mild FLHS and >50% as severe FLHS. The results showed that the levels of Cidea and Cidec mRNA expression were markedly elevated in the liver and adipose tissues with FLHS and the levels of Cidea and Cidec mRNA expression in the liver with severe FLHS were significantly higher than that in the liver with mild FLHS. Thus, the present study revealed that the Cidea and Cidec genes may be involved in pathways of FLHS formation.